Complementary and Alternative Therapy to Reduce Fatigue Among Oncology Patient under Chemotherapy : A Nursing Perspective - Ni Kadek Diah Purnamayanti; Muhammad G A Putra; Haryani Haryani (Faculty of Nursing, Universitas Hasanuddin, 2021)
The incidence of cancer is rapidly increasing among the world. Cancer mostly demand cytotoxic regiment that caused adverse events. Fatigue is the most symptom that complained by oncology patients. Nurse has obligation to relieve patient’s simptom and promote well being during the therapeutic procedure. The aim of this study was to analyse the effect of complementary and alternative therapy to reduce fatigue based on nursing perspective. Design of the study was literature review. Online searching method involved four databases including Pubmed, Sciendirect, SAGE, and Pubmed. The inclusion criteria of studies were published in free fulltext between 2012 and 2018, clinical experimental studies at least quasi experiment or RCT. The exclusion criteriawere not in adult population who received chemotherapy. The results found eight studies matched the criteria. There were two studies applied massage as body manipulation and exercise-energy based intervention such as acupressure, yoga, qigong, and taichi. Those intervention were relevant with nursing body of knowledge, well explained in the North American Nursing Diagnosis Association, Nursing Outcomes Classification, Nursing Interventions Classification (NANDA, NOC, and NIC) as standardized nursing language.